Seizures induced in immature rats by homocysteic acid and the associated brain damage are prevented by group II metabotropic glutamate receptor agonist (2R,4R)-4-aminopyrrolidine-2,4-dicarboxylate - Folbergrová, Jaroslava; Druga, Rastislav; Otáhal, Jakub; Haugvicová, Renata; Mares, Pavel; Kubová, Hana (Experimental neurology, 2005)
The present study has examined the anticonvulsant and neuroprotective effect of group II metabotropic glutamate receptor (mGluR) agonist (2R,4R)-4-aminopyrrolidine-2,4-dicarboxylate (2R,4R-APDC) in the model of seizures induced in immature 12-day-old rats by bilateral intracerebroventricular infusion of dl-homocysteic acid (DL-HCA, 600 nmol/side). For biochemical analyses, rat pups were sacrificed during generalized clonic-tonic seizures, approximately 45-50 min after infusion. Comparable time intervals were used for sacrificing the pups which had received 2R,4R-APDC. Low doses of 2R,4R-APDC (0.05 nmol/side) provided a pronounced anticonvulsant effect which was abolished by pretreatment with a selective group II mGluR antagonist LY341495. Generalized clonic-tonic seizures were completely suppressed and cortical energy metabolite changes which normally accompany these seizures were either normalized (decrease of glucose and glycogen) or markedly reduced (an accumulation of lactate). EEG recordings support the marked anticonvulsant effect of 2R,4R-APDC, nevertheless, this was only partial. In spite of the absence of obvious motor phenomena, isolated spikes or even short periods of partial ictal activity could be observed. Isolated spikes could also be seen in some animals after application of 2R,4R-APDC alone, reflecting most likely subclinical proconvulsant activity of this agonist. The neuroprotective effect of 2R,4R-APDC was evaluated after 24 h and 6 days of survival following DL-HCA-induced seizures. Massive neuronal degeneration, as revealed by Fluoro-Jade B staining, was observed in a number of brain regions following infusion of DL-HCA alone (seizure group), whereas 2R,4R-APDC pretreatment provided substantial neuroprotection. The present findings support the possibility that group II mGluRs are a promising target for a novel approach to treating epilepsy.
Keywords: funkční lateralita; Brain Injuries; novorozená zvířata; Functional Laterality; Glycogen; záchvaty; xantheny; Proline; elektroencefalografie; Glucose; zvířata; Nerve Degeneration; organické látky; fluorescenční barviva; receptory metabotropního glutamátu; degenerace nervu; Fluoresceins; Rats; Time Factors; Dose-Response Relationship, Drug; Receptors, Metabotropic Glutamate; homocystein; Behavior, Animal; mužské pohlaví; Homocysteine; antagonisté excitačních aminokyselin; Anticonvulsants; chování zvířat; prolin; Brain Chemistry; lékové interakce; časové faktory; Organic Chemicals; glukosa; Brain; mozek; vztah mezi dávkou a účinkem léčiva; Excitatory Amino Acid Antagonists; krysa rodu Rattus; fluoresceiny; Lactic Acid; glykogen; kyselina mléčná; mozek - chemie; Xanthenes; Rats, Wistar; Animals; Male; Amino Acids; Fluorescent Dyes; Drug Interactions; antikonvulziva; poranění mozku; Electroencephalography; Animals, Newborn; potkani Wistar; Seizures; aminokyseliny